2018
DOI: 10.1161/circulationaha.117.031542
|View full text |Cite
|
Sign up to set email alerts
|

Early Regenerative Capacity in the Porcine Heart

Abstract: -The adult mammalian heart has limited ability to repair itself following injury. Zebrafish, newts and neonatal mice can regenerate cardiac tissue, largely by cardiac myocyte (CM) proliferation. It is unknown if hearts of young large mammals can regenerate. -We examined the regenerative capacity of the pig heart in neonatal animals (ages: 2, 3 or 14 days postnatal) after myocardial infarction (MI) or sham procedure. Myocardial scar and left ventricular function were determined by cardiac magnetic resonance (CM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
175
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(187 citation statements)
references
References 31 publications
12
175
0
Order By: Relevance
“…[57][58][59] ). This decline in neonatal cardiac proliferative potential correlates with down-regulation of multiple genes involved in cell cycle 40,55,[60][61][62][63] , including endogenous Myc, which is high at P1 but significantly reduced by P5 ( Supplementary Fig. 6a).…”
Section: Discussionmentioning
confidence: 98%
“…[57][58][59] ). This decline in neonatal cardiac proliferative potential correlates with down-regulation of multiple genes involved in cell cycle 40,55,[60][61][62][63] , including endogenous Myc, which is high at P1 but significantly reduced by P5 ( Supplementary Fig. 6a).…”
Section: Discussionmentioning
confidence: 98%
“…Neonatal heart regeneration is mediated mainly by proliferation of preexisting cardiomyocytes and is supported by angiogenesis, macrophage infiltration, and innervation (8,9,11). Intriguingly, heart regeneration was reported in pigs and even in a human newborn after myocardial infarction (12)(13)(14). The neonatal cardiac regenerative capacity, however, is lost by P7 (7).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, adult zebrafish hearts are capable of mounting an endogenous regenerative program and are able to completely regenerate their myocardium through cardiomyocyte proliferation following ventricular resection (Poss et al 2002). This regenerative potential was found to be conserved in the mammalian heart, but only for a brief time after birth in both neonatal mice and pigs (Ye et al 2018;Zhu et al 2018). These models of endogenous cardiac regeneration revealed that regeneration is mediated by the proliferation of the pre-existing cardiomyocytes.…”
Section: Cholinergic Nerve Regulation Of Heart Regenerationmentioning
confidence: 99%